Turkish Norms of McNamara's Cephalometric Analysis - Halise Aydemir; Zaur Novruzov; Ufuk Toygar-Memikoğlu (Galenos Yayinevi, 2014)
Objective:(1) To establish cephalometric standards for the Turkish adult population, (2) to compare Turkish norms with the published standards of McNamara norms, and (3) to compare the assessment of craniofacial structure by extracranial and intracranial reference lines.Materials and Method:The main study sample consisted of 44 female and 29 male dental students aged between 19 and 29 years. All of the head films were taken in the natural head position, which was determined with 0.5-mm wire that was attached to a fluid level device to represent the true horizontal and a metal chain that was suspended in front of the cassette to check the true horizontal.Results:For men, N perp A and Pg N perp were significantly greater (p,0.001) in the Turkish population, whereas SNA (p,0.001), CoGn (p,0.001), CoA (p,0.001), upper incisal A vertical (p,0.05), and lower incisor A pg (p,0.05) were significantly smaller. In women, N perp A and Pg N perp were significantly greater (p,0.001) in the Turkish population, whereas SNA (p,0.01), CoGn (p,0.001), and CoA (p,0.01) were significantly smaller. For both men and women, only the variables FH/ GoMe and X1-X2/GoMe were compatible with each other (p,0.001).Conclusion:The Anotolian Turkish sample has shorter midfacial (Co-A) and mandibular (Co-Gn) lengths and a more protrusive maxilla (N perp A) and mandible (Pg N perp). Extracranial reference lines are more reliable than intracranial reference lines because of interindividual variability.